Critical role of Ror2 receptor tyrosine kinase in regulating cell cycle progression of reactive astrocytes following brain injury. Issue 1 (11th October 2016) - Endo, Mitsuharu; Ubulkasim, Guljahan; Kobayashi, Chiho; Onishi, Reiko; Aiba, Atsu; Minami, Yasuhiro
Abstract : Ror2 receptor tyrosine kinase plays crucial roles in developmental morphogenesis and tissue‐/organo‐genesis. In the developing brain, Ror2 is expressed in neural stem/progenitor cells (NPCs) and involved in the regulation of their stemness. However, it remains largely unknown about its role in the adult brain. In this study, we show that Ror2 is up‐regulated in reactive astrocytes in the neocortices within 3 days following stab‐wound injury. Intriguingly, Ror2‐expressing astrocytes were detected primarily at the area surrounding the injury site, where astrocytes express Nestin, a marker of NPCs, and proliferate in response to injury. Furthermore, we show by using astrocyte‐specific Ror2 knockout (KO) mice that a loss of Ror2 in astrocytes attenuates injury‐induced proliferation of reactive astrocytes. It was also found that basic fibroblast growth factor (bFGF) is strongly up‐regulated at 1 day post injury in the neocortices, and that stimulation of cultured quiescent astrocytes with bFGF restarts their cell cycle and induces expression of Ror2 during the G1 phase predominantly in proliferating cells. By using this culture method, we further show that the proportions of Ror2 ‐expressing astrocytes increase following treatment with the histone deacetylases inhibitors including valproic acid, and that bFGF stimulation increases the levels of Ror2 expression within the respective cells. Moreover, we show that bFGF‐induced cell cycle progression into S phase is inhibited or promoted in astrocytes from Ror2 KO mice or NPCs stably expressing Ror2‐GFP, respectively. Collectively, these findings indicate that Ror2 plays a critical role in regulating the cell cycle progression of reactive astrocytes following brain injury, GLIA 2016. GLIA 2017;65:182–197 Main Points: Ror2 is up‐regulated in reactive astrocytes in the neocortices following brain injury. Loss of Ror2 attenuates injury‐induced proliferation of reactive astrocytes. bFGF might contribute to induce expression of Ror2 in reactive astrocytes.